An analysis of the competitive actions of Boeing and Airbus in the aerospace industry based on the competitive dynamics model - Ayoung Woo; Bokyung Park; Hyekyung Sung; Hyunjin Yong; Jiyeon Chae; Seungho Choi (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Focusing on competitive dynamics, this study examines the strategic issues Boeing has faced in seeking to maintain its leading position in the airline industry. Boeing's status as a first mover in the aerospace industry has made it a world-leading company; however, the external environment and various pressures have allowed Airbus to emerge as a strong competitor. By conducting a descriptive case analysis, this paper identifies the competitive issues between these two giants, analyzing continuous action and reaction processes throughout the whole history of the airline industry. Finally, by examining Boeing's main strengths, business diversification options, and risk-taking culture, this paper suggests ways Boeing can retake its place as the industry leader.
Keywords: 650; action and reaction; aerospace industry; Airbus; Boeing; competitive dynamics; first mover advantage; open innovation